Turbo equalization and its improvement in BICM-ID based on hard-decision - ZHAO Chun-hui1; LV Qiang1; BI Wen-bin2 (Tongxin xuebao)
Conventional receivers executed equalization and channel decoding independently. Turbo equalization was a technique which combined equalization and decoding. It got better performance by exchanging the extrinsic information iteratively between the equalizer and decoder. The SIC algorithm of Turbo equalization to BICM-ID system based on hard-decision was applied and an improved method was also proposed. Simulation results show that this algorithm leads to convergence in ISI channels with different fading degree and it approaches the performance in AWGN gradually along with the increasing SNR.